Anthropometric study on the nasofrontal angle in human skulls - Yas, Nawfal K. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: The nasofrontal angle is the angle between the forehead & dorsum of the nose, it is of prime importance in giving the shape of the nose in relation to face. Workers studied this angle in living individuals, in this work, the angle was measured on dry human skulls, in addition, its value was statistically correlated with certain facial parameters.Objectives: Determination of the value of nasofrontal angle in human skulls & correlation of this value to other facial parameters, namely; length of nasal bone, nasion height & midfacial length as these parameters are important for surgeons working in rhinoplasty.Methods: The nasofrontal angle & other facial parameters were measured carefully on dry human skulls, their values were recorded & statistical correlation between them was performed.Results: Nasal bone length showed a strong correlation with the values of nasofrontal angle, nasion height & midfacial length.Conclusion: Nasal bone length may play an important role in determination of other facial parameters & may play a role in the indications for rhinoplasty.